Sensitivitas Organisasi NU dan Muhammadiyah dalam Pengembangan Dakwah (Studi Kasus di Kecamatan Bangah Kabupaten Sidoarjo) - Zainul Abidin Zamroni; Moh. Abdul Wahab Tsalatsa (QULUBANA: Jurnal Manajemen Dakwah, 2021)
The Nahdlatul Ulama and Muhammadiyah Associations are the 2 large associations located in Sidoarjo, the success of this Islamic Association in missions and delegations is not dated according to the use of good delegation tactics. The beautiful key will be carried by the beautiful vehicle / media vehicle. Nahdlatul Ulama and Muhammadiyah in Sidoarjo Regency. The following observations use the method of accumulation to study information that leads to a description of the qualitative observation method, to obtain files that reply to the completed case definition, regarding the analogy of social media utilization tactics on delegation between the two observation objectives. Then the output according to this observation will be met in the application of an analogy tool to understand the similarities and differences, and the disadvantages and advantages of the two observations made above. Meanwhile advantages and disadvantages. The advantages of the following 2 associations in riding social media are in the system of utilizing a single social media handling scheme & coordinating collaboration using social media and other community media